Recreational boat traffic effects on fish assemblages: First evidence of detrimental consequences at regulated mooring zones in sensitive marine areas detected by passive acoustics. (1st February 2019) - González Correa, José Miguel; Bayle Sempere, Just-Tomás; Juanes, Francis; Rountree, Rodney; Ruíz, Juan Francisco; Ramis, Jaime
Abstract: We assess the impact of recreational boat traffic on sensitive habitats in the Western Mediterranean using passive acoustics. We compared underwater sounds in three regulated mooring locations vs a pristine location; and temporal differences in the pristine location vs the nearest mooring between high and low touristic seasons. We measured the number of pulses/minute, fish pulse patterns, and percentage of boat noise occurrence and its relative average power level. At the pristine location, the call rates and their complexity were significantly higher and the motorboat noise was significantly lower. The temporal trend of biophonic sounds decreased significantly in the pristine location. In contrast, in the mooring sites, the motorboat noise decreased significantly and the fish calls remained at low levels in both seasons. In conclusion, motorboat noise negatively affects the complexity of the fish assemblages but could be conditioned to their historic uses. Highlights: High motorboat noise negatively affects the biophonic complexity of the fish assemblage but conditioned to the specific circumstances of each locality in terms of their historic uses. Two dominant fish calls were described. Passive acoustics is a useful tool to distinguish different ecological fish assemblages through sound complexity. The different types of boating activity observed at the three mooring locations likely result in boat noise levels that mirror the boat noise occurrence pattern.